A long history in a short note—identity and typification of the name Hippion obtusifolium F.W. Schmidt, and synonymy of the species Gentianella obtusifolia (Gentianaceae) - Reich, Dieter; Mráz, Patrik; Šída, Otakar; Gutermann, Walter (Phytotaxa, 2023)
The description of Hippion obtusifolium F.W. Schmidt was followed by more than 200 years of confusion concerning the identity of this taxon, the origin of the material it is based on, and its typification. Hereby, we briefly summarize this historical development, clarify the typification and the identity of the taxon currently known as Gentianella obtusifolia and designate an epitype to stabilize the application of the name having priority over G. aspera. Additionally, the morphological characterization and geographic distribution of the taxon are discussed and an exhaustive synonymy is provided.